The Oxford handbook of the book of Revelation - Koester, Craig R. 1953- (Oxford Oxford University Press, Incorporated, 2020)
The Book of Revelation holds a special fascination for both scholars and the general public. The book has generated widely differing interpretations, yet Revelation has surprisingly not been the focus of many single-volume reference works. The Oxford Handbook of the Book of Revelation fills a need in the study of this controversial book.
Cover -- The Oxford Handbook of The Book of Revelation -- Copyright -- Contents -- Preface -- List of Contributors -- Abbreviations -- Chapter 1: Introduction to Revelation's Social Setting, Theological Perspective, and Literary Design -- 1. The Writer's Identity and Social Setting -- The Writer's Social Setting and Time Frame -- 2. Social Patterns and the Readers of Revelation -- Conflict with Those Outside the Community -- Internal Disputes over Accommodation of Greco-Roman Religious Practices -- Wealth and Complacency -- 3. Revelation's Theological Perspectives and Imagery -- God, the Lamb, the Witnesses, and New Jerusalem -- Satan, the Beast, the False Prophet, and Babylon -- 4. The Literary Structure and Movement of Revelation -- The First Three Cycles (Rev 1:9-11:18) -- The Last Three Cycles (11:19-22:5) -- 5. Conclusion -- Notes -- Part I: Literary Features of the book of Revelation -- Chapter 2: The Genre of the Book of Revelation -- Revelation as an Apocalypse -- Revelation as a Letter -- Revelation as a Prophecy -- Conclusion -- References -- Chapter 3: Narrative Features of the Book of Revelation -- Revelation's Masterplot -- Characters and Characterization -- Architectural and Topographical Settings -- Numerical Symbolism -- Conclusion -- Notes -- References -- Chapter 4: Imagery in the Book of Revelation -- Different Types of Figurative Speech -- From Word Pictures to a Symphony of Images -- The Multifaceted Background of the Images -- Function and Effect of the Imagery -- Impacts on the History of Reception -- Conclusion -- References -- Chapter 5: Rhetorical Features of the Book of Revelation -- Introduction: Revelation as a "Rhetorical" Text -- John's Principal Rhetorical Goals -- John's Construction of Authority (Ethos) -- John's Appeals to the Emotions (Pathos) -- Appeals to Rational Argument (Logos) in Revelation -- Conclusion.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Aufsatzsammlung